Preparation method of high-strength semi-solid lithium battery diaphragm
By adopting a high-strength semi-solid lithium battery separator preparation method composed of a fast ion transport layer and a stable layer, the existing separator has solved the problem of deformation, liquid leakage and low safety performance during use, and achieved higher thermal stability and safety.
Patent Information
- Application Number
- CN202411917982.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-21
AI Technical Summary
The existing semi-solid lithium battery separators are prone to deformation, liquid leakage and low safety performance due to collision or high temperature during use.
A high-strength semi-solid lithium battery separator preparation method consisting of a fast ion transport layer and a stable layer is adopted. The transport layer consists of an active skeleton and a gel matrix, and the stable layer consists of a gel matrix and an inert framework, and the final separator is synthesized by hot pressing.
It improves the thermal stability of the diaphragm, enhances the safety and service life of the battery, reduces deformation of the internal structure of the battery, prevents battery short circuit, and ensures safe use of the battery.
Smart Images

Figure BDA0005207245770000101 
Figure BDA0005207245770000111 
Figure BDA0005207245770000112
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery separators, and in particular to a method for preparing a high-strength semi-solid lithium battery separator. Background Art
[0002] In semi-solid batteries, polyethylene oxide (polymer suspension) is a polymer electrolyte with great application prospects due to its unique lithium ion mobility and is the main raw material for preparing semi-solid battery separators.
[0003] A Chinese patent with publication number CN111416087A discloses a novel method for preparing a semi-solid lithium battery separator by heat radiation cross-linking. A cross-linking agent is added to a semi-solid electrolyte containing polyethylene glycol, and then the semi-solid electrolyte is evenly coated on both sides of a polymer base film. Through the heat radiation of an oven, the polyethylene glycol and the base film undergo a cross-linking reaction under the action of the cross-linking agent, thereby solving the problem of uneven diffusion of the electrolyte leading to a decrease in battery electrical performance.
[0004] The above patent solves the problem of battery performance degradation by adding a cross-linking agent to carry out a cross-linking reaction. However, since the battery is subjected to collision or high temperature during use, it will cause the battery to deform, leak, or even fail, and the safety performance is not high. Therefore, it does not meet the existing needs. In this regard, we propose a method for preparing a high-strength semi-solid lithium battery separator. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a high-strength semi-solid lithium battery separator, so that the prepared semi-solid lithium battery separator has higher thermal stability, improves the safety and service life of the battery, further enhances the performance of the semi-solid lithium battery separator, reduces the deformation of the internal structure of the battery, thereby enhancing the overall stability of the battery, and can effectively prevent the battery from short circuiting and protect the battery from damage when facing external impacts or pressure changes, thereby ensuring the safe use of the battery and solving the problems raised in the above-mentioned background technology.
[0006] To achieve the above object, the present invention provides the following technical solution: a method for preparing a high-strength semi-solid lithium battery separator, wherein the high-strength semi-solid lithium battery separator is composed of a fast ion transport layer and a stabilizing layer, wherein the transport layer is composed of an active skeleton and a gel matrix, and the stabilizing layer is composed of a gel matrix and an inert skeleton, and the method for preparing the high-strength semi-solid lithium battery separator comprises the following steps:
[0007] S1: Preparation of 3D nanostructured LLTO active skeleton and preparation of gel matrix;
[0008] S2: embedding the gel matrix into the active skeleton to form a fast ion transport layer with skeleton support;
[0009] S3: embedding the gel matrix into an inert skeleton to form a stable layer with skeleton support;
[0010] S4: The fast ion transport layer and the stabilization layer are combined together by hot pressing to form the final semi-solid lithium battery separator.
[0011] Preferably, the preparation method of the 3D nanostructured LLTO active skeleton is as follows:
[0012] preparing a precursor solution of LLTO, adding an appropriate amount of PVA, a cross-linking agent and an initiator to the LLTO precursor solution, and gelling the solution to form a 3D nanostructured LLTO hydrogel;
[0013] The formed LLTO hydrogel was heat-treated at 800 °C in air for 2 h to form a porous active skeleton.
[0014] The LLTO precursor was mixed with polyvinyl alcohol and gelled by a cross-linker and an initiator to synthesize a 3D nanostructured LLTO hydrogel;
[0015] The dried LLTO hydrogel was heat treated at 800 °C in air for 2 h to form a 3D skeleton.
[0016] Preferably, the cross-linking agent is selected from any cross-linking agent in the group consisting of: CDAP, EDC, sodium cyanoborohydride, cyanogen bromide and ammonium bicarbonate / iodoacetic acid.
[0017] Preferably, the preparation of the precursor solution of LLTO specifically comprises:
[0018] Selecting compounds containing lithium, lanthanum and tantalum as precursor materials;
[0019] Add the precursor material and the surfactant into the organic solvent for mixing, and adjust the ratio of the precursor material and the solvent according to the LLTO concentration;
[0020] After the adjustment is completed, the mixed solution is heated and stirred to form a uniform precursor solution;
[0021] The precursor solution is filtered and purified to obtain a pure LLTO precursor solution, and a surfactant is added.
[0022] Preferably, the preparation method of the inert skeleton is as follows:
[0023] Adding siloxane to the polyamic acid organic solution and stirring thoroughly to obtain an organic solution;
[0024] The organic solution is uniformly coated on the substrate, and dried naturally at room temperature to remove the solvent to form a nanoporous polyimide membrane;
[0025] The nanoporous polyimide membrane was heat treated at 280-300°C for 2 hours to form an inert skeleton.
[0026] Preferably, the preparation of the gel matrix specifically includes: dissolving the polymer suspension, nanoceramics, organic polymer compounds and inorganic metal salts in a predetermined ratio to prepare the gel matrix of the fast ion transport layer.
[0027] Preferably, the preparation process of the polymer suspension specifically includes: uniformly mixing PEO, PMMA and a diluent in proportion, stirring to form a polymer suspension, wherein the diluent is one or a combination of phthalates, aromatic ethers, white oil and wax to form a uniform and stable suspended polymer.
[0028] Preferably, the materials used to prepare the fast ion transport layer and the stabilizing layer also include a plasticizer, and the plasticizer is at least one of DEHP, DOP and DBP.
[0029] Preferably, the organic polymer compound is one of LiTFSI, polyacrylic acid, sodium polyacrylate and sodium carboxymethyl cellulose.
[0030] Preferably, the inorganic metal salt is one of calcium chloride, zinc chloride, zinc acetate and aluminum chloride.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] The present invention adds nano-ceramic powder to make the semi-solid lithium battery separator have higher thermal stability, prevent the battery from being damaged due to overheating, thereby improving the safety of the battery, increasing the service life of the battery, and further enhancing the performance of the semi-solid lithium battery separator. By adjusting the concentration of PMMA, it can better withstand external pressure and impact, reduce the deformation of the internal structure of the battery, thereby enhancing the overall stability of the battery, and effectively prevent the battery from short circuiting and protecting the battery from damage when facing external impact or pressure changes, thereby ensuring the safe use of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 The present invention is a process flow chart of a method for preparing a high-strength semi-solid lithium battery separator. DETAILED DESCRIPTION
[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] Embodiment 1:
[0036] In order to solve the problem of the existing patent that the battery electrical performance is reduced by adding a cross-linking agent to perform a cross-linking reaction, but the battery is subject to collision or high temperature during use, which may cause the battery to deform, leak or even fail, and the safety performance is not high. Please refer to Figure 1 , this embodiment provides the following technical solutions:
[0037] A method for preparing a high-strength semi-solid lithium battery separator, the high-strength semi-solid lithium battery separator is composed of a fast ion transport layer and a stabilizing layer, wherein the transport layer is composed of an active skeleton and a gel matrix, and the stabilizing layer is composed of a gel matrix and an inert skeleton. The method for preparing the high-strength semi-solid lithium battery separator comprises the following steps:
[0038] S1: Prepare 3D nanostructured LLTO active skeleton and gel matrix, directly mix solid electrolyte and binder into film, no drying is required, which is more cost-effective.
[0039] The preparation method of the 3D nanostructured LLTO active skeleton is as follows:
[0040] preparing a precursor solution of LLTO, adding an appropriate amount of PVA, a cross-linking agent and an initiator to the LLTO precursor solution, and gelling the solution to form a 3D nanostructured LLTO hydrogel;
[0041] The formed LLTO hydrogel was heat-treated at 800 °C in air for 2 h to form a porous active skeleton.
[0042] The LLTO precursor was mixed with polyvinyl alcohol and gelled by a cross-linker and an initiator to synthesize a 3D nanostructured LLTO hydrogel;
[0043] The dried LLTO hydrogel was heat treated at 800 °C in air for 2 h to form a 3D skeleton.
[0044] The cross-linking agent is selected from any cross-linking agent in the group consisting of CDAP, EDC, sodium cyanoborohydride or cyanogen bromide, and ammonium bicarbonate / iodoacetic acid.
[0045] The precursor solution of LLTO is prepared, specifically comprising:
[0046] Selecting compounds containing lithium, lanthanum and tantalum as precursor materials;
[0047] Add the precursor material and the surfactant into the organic solvent and mix them. Adjust the ratio of the precursor material and the solvent according to the LLTO concentration to ensure that the precursor material is completely dissolved.
[0048] After the adjustment is completed, the mixed solution is heated and stirred to form a uniform precursor solution;
[0049] The precursor solution is filtered and purified to obtain a pure LLTO precursor solution, and a surfactant is added to maintain the dispersibility of the LLTO particles and prevent the LLTO particles from aggregating in the solution.
[0050] The preparation method of the inert skeleton is as follows:
[0051] In a polyamic acid organic solution with a mass percentage concentration of 5 to 30%, siloxane is added at a mass ratio of 100:1 to 30 for polyamic acid to siloxane, and the organic solution is obtained after sufficient stirring, wherein the solvent used to prepare the polyamic acid organic solution is dimethylacetamide, dimethylformamide, N-methylpyrrolidone or a mixed solvent of tetrahydrofuran and methanol, the obtained organic solution is allowed to stand, bubbles generated during the preparation process are removed, and then a film is made and dried, and the obtained film is heat-treated at 280 to 320° C. for more than 2 hours to obtain a polyimide / nano-silicon dioxide composite film. This method has the characteristics of simple process, low cost, high strength, good heat resistance, etc.
[0052] The organic solution is uniformly coated on the substrate, and dried naturally at room temperature to remove the solvent to form a nanoporous polyimide membrane;
[0053] The nanoporous polyimide membrane was heat treated at 280-300°C for 2 hours to form an inert skeleton.
[0054] The preparation of the gel matrix specifically includes: dissolving the polymer suspension, nano-ceramics, organic polymer compounds and inorganic metal salts according to a predetermined ratio to prepare the gel matrix of the fast ion transport layer.
[0055] The preparation process of the polymer suspension specifically includes: uniformly mixing PEO, PMMA and a diluent in a mass ratio of 1-3:3-6:2-6, and stirring to form a polymer suspension, wherein the viscosity-average molecular weight of the ultra-high molecular weight polyethylene resin is 50,000 to 3.5 million, and the diluent is one or a combination of phthalates, aromatic ethers, white oils and waxes to form a uniform and stable suspended polymer.
[0056] The materials for preparing the fast ion transport layer and the stabilizing layer also include a plasticizer, and the plasticizer is at least one of DEHP, DOP and DBP.
[0057] The organic polymer compound is one of LiTFSI, polyacrylic acid, sodium polyacrylate and sodium carboxymethyl cellulose.
[0058] The inorganic metal salt is one of calcium chloride, zinc chloride, zinc acetate and aluminum chloride.
[0059] Fast ion transport layer, thickness: 15 μm, composition as follows:
[0060] Polymer suspension: 10wt%
[0061] Polyacrylamide (DEHP): 30wt%
[0062] LiTFSI: 5wt%
[0063] Calcium chloride: 5wt%
[0064] Nano ceramics: 10wt%
[0065] Active skeleton: 40wt%;
[0066] Stabilization layer, thickness: 35 μm, composed as follows:
[0067] Polymer suspension: 20wt%
[0068] DEHP: 10wt%
[0069] LiTFSI: 5wt%
[0070] Calcium chloride: 50wt%
[0071] Nano ceramics: 10wt%
[0072] Inert skeleton: 5wt%
[0073] S2: PEO, PMMA and diluent are uniformly mixed in a mass ratio of 3:5:2 to form a polymer suspension, the prepared polymer suspension, DEHP, LiTFSI, calcium chloride and nano-ceramics are dissolved in N,N-dimethylformamide in proportion to prepare a gel matrix of the transmission layer, the gel matrix is embedded into the active skeleton, and it is dried to form a transmission layer with skeleton support;
[0074] S3: dissolving the polymer suspension, DEHP, LiTFSI, calcium chloride and nano-ceramics in S2 into N,N-dimethylformamide in proportion to prepare a gel matrix of the stabilizing layer, embedding the gel matrix into the active skeleton, and drying it to form a stabilizing layer supported by the skeleton;
[0075] S4: The fast ion transport layer and the stabilization layer are combined together by hot pressing to form the final semi-solid lithium battery separator.
[0076] Example 2
[0077] PEO, PMMA and a diluent were uniformly mixed in a mass ratio of 3:5:2 to form a polymer suspension, 15wt% of the polymer suspension, 35wt% of DEHP, 5wt% of LiTFSI, 5wt% of calcium chloride and 5wt% of nano-ceramics were dissolved in N,N-dimethylformamide to prepare a gel matrix of a fast ion transport layer, and an active skeleton was prepared by the method of Example 1, 45wt% of the active skeleton was taken as a supporting skeleton, the gel matrix was embedded in the active skeleton, and a fast ion transport layer supported by a skeleton was formed after drying. The fast ion transport layer after drying had a thickness of 12μm.
[0078] The polymer suspension prepared in the above proportions: 20wt%, DEHP: 10wt%, LiTFSI: 5wt%, calcium chloride: 55wt%, and nano-ceramics 5wt% were dissolved in N,N-dimethylformamide to prepare a gel matrix for the stabilization layer. The inert skeleton was prepared by the same method as in Example 1, 5wt% of the inert skeleton was taken as the supporting skeleton, and the gel matrix was embedded in the active skeleton. After drying, a stabilization layer supported by the skeleton was formed, and the thickness of the stabilization layer was 35μm.
[0079] The fast ion transport layer and the stabilizing layer are combined together by hot pressing to form the final semi-solid lithium battery separator.
[0080] Embodiment 3:
[0081] PEO, PMMA and a diluent are uniformly mixed in a mass ratio of 2:4:4 to form a polymer suspension, 10wt% of the polymer suspension, 30wt% of DOP, 5wt% of polyacrylic acid, 5wt% of zinc chloride and 10wt% of nano-ceramics are dissolved in N,N-dimethylformamide to prepare a gel matrix of a fast ion transport layer, and an active skeleton is prepared by the method of Example 1, 40wt% of the active skeleton is taken as a supporting skeleton, the gel matrix is embedded in the active skeleton, and a fast ion transport layer supported by a skeleton is formed after drying. The fast ion transport layer after drying has a thickness of 10μm.
[0082] The polymer suspension prepared in the above proportions: 20wt%, DOP: 10wt%, polyacrylic acid: 5wt%, zinc chloride: 50wt%, and nano-ceramics 10wt% were dissolved in N,N-dimethylformamide to prepare a gel matrix for the stabilizing layer. The inert skeleton was prepared by the same method as in Example 1, 10wt% of the inert skeleton was taken as the supporting skeleton, and the gel matrix was embedded in the active skeleton. After drying, a stabilizing layer supported by the skeleton was formed, and the thickness of the stabilizing layer was 36μm.
[0083] The fast ion transport layer and the stabilizing layer are combined together by hot pressing to form the final semi-solid lithium battery separator.
[0084] Embodiment 4:
[0085] PEO, PMMA and a diluent are uniformly mixed in a mass ratio of 2:4:4 to form a polymer suspension. 15wt% of the polymer suspension, 25wt% of DOP, 5wt% of polyacrylic acid, 10wt% of zinc chloride and 5wt% of nano-ceramics are dissolved in N,N-dimethylformamide to prepare a gel matrix of a fast ion transport layer. An active skeleton is prepared by the method of Example 1. 40wt% of the active skeleton is used as a supporting skeleton. The gel matrix is embedded in the active skeleton. After drying, a fast ion transport layer supported by a skeleton is formed. The fast ion transport layer after drying has a thickness of 12μm.
[0086] Take a polymer suspension: 25wt%, DOP: 15wt%, polyacrylic acid: 5wt%, zinc chloride: 50wt% and dissolve them in N,N-dimethylformamide to prepare a gel matrix of the stabilizing layer. The inert skeleton is prepared by the same method as in Example 1, 5wt% of the inert skeleton is taken as the supporting skeleton, and the gel matrix is embedded in the active skeleton. After drying, a stabilizing layer supported by the skeleton is formed, and the thickness of the stabilizing layer is 38μm.
[0087] The fast ion transport layer and the stabilizing layer are combined together by hot pressing to form the final semi-solid lithium battery separator.
[0088] Embodiment 5:
[0089] PEO, PMMA and a diluent are uniformly mixed in a mass ratio of 1:3:6 to form a polymer suspension, 20wt% of the polymer suspension, 30wt% of DBP, 5wt% of sodium carboxymethyl cellulose and 10wt% of aluminum chloride are dissolved in N,N-dimethylformamide to prepare a gel matrix of a fast ion transport layer, and an active skeleton is prepared by the method of Example 1, 35wt% of the active skeleton is taken as a supporting skeleton and immersed in the gel matrix, after two immersions, the remaining gel matrix is sprayed on the active skeleton, and a fast ion transport layer supported by a skeleton is formed after drying, and the fast ion transport layer after drying has a thickness of 10μm.
[0090] The polymer suspension prepared in the above proportions: 20wt%, DBP: 10wt%, sodium carboxymethyl cellulose: 5wt%, aluminum chloride: 60wt% was dissolved in N,N-dimethylformamide to prepare a gel matrix for the stabilizing layer. The inert skeleton was prepared by the same method as in Example 1, 5wt% of the inert skeleton was taken as the supporting skeleton, the gel matrix was embedded in the active skeleton, and a stabilizing layer supported by the skeleton was formed after drying. The thickness of the stabilizing layer was 30μm.
[0091] The fast ion transport layer and the stabilizing layer are combined together by hot pressing to form the final semi-solid lithium battery separator.
[0092] Embodiment 6:
[0093] PEO, PMMA and a diluent are uniformly mixed in a mass ratio of 1:3:6 to form a polymer suspension, 15wt% of the polymer suspension, 40wt% of DBP, 5wt% of sodium carboxymethyl cellulose and 5wt% of aluminum chloride are dissolved in N,N-dimethylformamide to prepare a gel matrix of a fast ion transport layer, and an active skeleton is prepared by the method of Example 1, 35wt% of the active skeleton is taken as a supporting skeleton and immersed in the gel matrix, after two immersions, the remaining gel matrix is sprayed on the active skeleton, and a fast ion transport layer supported by a skeleton is formed after drying, and the fast ion transport layer after drying has a thickness of 14μm.
[0094] The polymer suspension prepared in the above proportions: 20wt%, DBP: 10wt%, sodium carboxymethyl cellulose: 5wt%, aluminum chloride: 60wt% was dissolved in N,N-dimethylformamide to prepare a gel matrix for the stabilizing layer. The inert skeleton was prepared by the same method as in Example 1, 5wt% of the inert skeleton was taken as the supporting skeleton, the gel matrix was embedded in the active skeleton, and a stabilizing layer supported by the skeleton was formed after drying. The thickness of the stabilizing layer was 30μm.
[0095] The fast ion transport layer and the stabilizing layer are combined together by hot pressing to form the final semi-solid lithium battery separator.
[0096] The semi-solid lithium battery separators processed in the above-mentioned Examples 1, 3 and 5 were subjected to bending tests:
[0097] Sample preparation: A semi-solid lithium battery membrane with a size of 100 mm x 50 mm was selected as the test sample;
[0098] Equipment preparation: Use a bending test machine with an adjustable bending radius;
[0099] Environmental conditions: Ensure that the test environment temperature is stable at 25℃±2℃;
[0100] Setting parameters: Set the bending radius to 10mm and the bending angle to 180°;
[0101] Pretreatment: Leave the sample at room temperature for at least 2 hours to ensure that it reaches stable environmental conditions;
[0102] Install the sample: Fix the sample on the testing machine and ensure that the center position of the sample is aligned with the bending axis;
[0103] Start the test: Start the testing machine and perform the bending operation at a constant speed until the sample completes a 180° bend;
[0104] Repeated test: 10 cycles of testing were performed to evaluate the cyclic bending performance.
[0105]
[0106]
[0107] It can be concluded from the above table that although different materials are used to prepare the semi-solid lithium battery separators in Example 1, Example 3 and Example 5, the prepared semi-solid lithium battery separators have little difference in appearance performance. Although no cracks, peeling, deformation and expansion are found after the bending test, there are still slight differences in the mechanical properties of the semi-solid lithium battery separators. Compared with Example 2 and Example 3, Example 1 increases the concentration of PMMA, so the prepared semi-solid lithium battery separator has better elastic modulus and recovery ability.
[0108] The tensile strength and puncture strength tests were performed on the semi-solid lithium battery separators processed in Example 1, Example 3, and Example 5;
[0109] Start the test: Clamp the sample and start the testing machine to stretch the sample until it breaks or reaches the preset tensile strength;
[0110] Spread the sample flat in the fixture, clamp it, install the puncture needle, and puncture at a rate of 100±10mm / min;
[0111] The puncture needle moves to puncture the sample at the set test speed. The testing machine displays the force value changes in real time and reports the puncture force value at the end of the test.
[0112] Repeated test: 10 cycles of testing to evaluate tensile strength and puncture strength;
[0113] The following test data were obtained:
[0114]
[0115] It can be concluded from the above table that nano-ceramic powder is added to Examples 1 and 3, so compared with the semi-solid lithium battery separator prepared in Example 5, the longitudinal tensile strength, transverse tensile strength and puncture strength are higher. At the same time, the concentration of PMMA in Example 1 is higher than the concentration of PMMA in Example 2. Therefore, the semi-solid lithium battery separator prepared in Example 1 is stronger than the semi-solid lithium battery separator prepared in Example 3.
[0116] The sample materials after the bending performance test were used in lithium batteries, and the following data were obtained after testing:
[0117]
[0118] After the impact resistance test, the semi-solid lithium battery separator prepared by increasing the concentration of PMMA and adding ceramic powder has better resistance to mechanical shock, thermal shock, vibration shock and pressure shock.
[0119] In summary, a high-strength semi-solid lithium battery separator preparation method of the present invention directly mixes solid electrolyte and binder into a film, does not need to be dried, and has more advantages in cost. By adding nano-ceramic powder, the semi-solid lithium battery separator prepared has higher thermal stability, effectively preventing the semi-solid lithium battery separator from shrinking and melting under thermal runaway conditions, and preventing the battery from being damaged by overheating, thereby improving the safety of the battery, increasing the service life of the battery, and further enhancing the performance of the semi-solid lithium battery separator. By adjusting the concentration of PMMA, it can better withstand external pressure and impact, reduce the deformation of the internal structure of the battery, and thus enhance the overall stability of the battery. In addition, the high-strength semi-solid lithium battery separator can also improve the safety performance of the battery, especially in the face of external impact or pressure changes, it can effectively prevent the battery from short circuiting and protect the battery from damage, thereby ensuring the safe use of the battery. At the same time, DEHP, DBP and DOP are used as plasticizers, and the bonding force is higher, avoiding affecting the overall performance and stability of the semi-solid lithium battery separator.
[0120] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0121] While the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that many changes, modifications, substitutions and variations can be made to the embodiments without departing from the principles and spirit of the invention.
Claims
1. A method for preparing a high-strength semi-solid lithium battery separator, characterized in that: The high-strength semi-solid lithium battery separator is composed of a fast ion transport layer and a stabilizing layer, wherein the transport layer is composed of an active skeleton and a gel matrix, and the stabilizing layer is composed of a gel matrix and an inert skeleton. The preparation method of the high-strength semi-solid lithium battery separator comprises the following steps: S1: Preparation of 3D nanostructured LLTO active skeleton and preparation of gel matrix; S2: embedding the gel matrix into the active skeleton to form a fast ion transport layer with skeleton support; S3: embedding the gel matrix into an inert skeleton to form a stable layer with skeleton support; S4: The fast ion transport layer and the stabilization layer are combined together by hot pressing to form the final semi-solid lithium battery separator.
2. The method for preparing a high-strength semi-solid lithium battery separator according to claim 1, characterized in that: The preparation method of the 3D nanostructured LLTO active skeleton is as follows: preparing a precursor solution of LLTO, adding an appropriate amount of PVA, a cross-linking agent and an initiator to the LLTO precursor solution, and gelling the solution to form a 3D nanostructured LLTO hydrogel; The formed LLTO hydrogel was heat-treated at 800 °C in air for 2 h to form a porous active skeleton. The LLTO precursor was mixed with polyvinyl alcohol and gelled by a cross-linker and an initiator to synthesize a 3D nanostructured LLTO hydrogel; The dried LLTO hydrogel was heat treated at 800 °C in air for 2 h to form a 3D skeleton.
3. The method for preparing a high-strength semi-solid lithium battery separator according to claim 2, characterized in that: The cross-linking agent is selected from any cross-linking agent in the group consisting of CDAP, EDC, sodium cyanoborohydride, cyanogen bromide, and ammonium bicarbonate / iodoacetic acid.
4. The method for preparing a high-strength semi-solid lithium battery separator according to claim 3, characterized in that: The preparation of the precursor solution of LLTO specifically comprises: Selecting compounds containing lithium, lanthanum and tantalum as precursor materials; Add the precursor material and the surfactant into the organic solvent for mixing, and adjust the ratio of the precursor material and the solvent according to the LLTO concentration; After the adjustment is completed, the mixed solution is heated and stirred to form a uniform precursor solution; The precursor solution is filtered and purified to obtain a pure LLTO precursor solution, and a surfactant is added.
5. The method for preparing a high-strength semi-solid lithium battery separator according to claim 1, characterized in that: The preparation method of the inert skeleton is as follows: Adding siloxane to the polyamic acid organic solution and stirring thoroughly to obtain an organic solution; The organic solution is uniformly coated on the substrate, and dried naturally at room temperature to remove the solvent to form a nanoporous polyimide membrane; The nanoporous polyimide membrane was heat treated at 280-300°C for 2 hours to form an inert skeleton.
6. The method for preparing a high-strength semi-solid lithium battery separator according to claim 1, characterized in that: The preparation of the gel matrix specifically includes: dissolving the polymer suspension, nano-ceramics, organic polymer compounds and inorganic metal salts according to a predetermined ratio to prepare the gel matrix of the fast ion transport layer.
7. A method for preparing a high-strength semi-solid lithium battery separator according to claim 6, characterized in that: The preparation process of the polymer suspension specifically comprises: uniformly mixing PEO, PMMA and a diluent in proportion, and stirring to form a polymer suspension, wherein the diluent is one or a combination of phthalate, aromatic ether, white oil and wax.
8. The method for preparing a high-strength semi-solid lithium battery separator according to claim 6, characterized in that: The materials for preparing the fast ion transport layer and the stabilizing layer also include a plasticizer, and the plasticizer is at least one of DEHP, DOP and DBP.
9. The method for preparing a high-strength semi-solid lithium battery separator according to claim 6, characterized in that: The organic polymer compound is one of LiTFSI, polyacrylic acid, sodium polyacrylate and sodium carboxymethyl cellulose.
10. The method for preparing a high-strength semi-solid lithium battery separator according to claim 6, characterized in that: The inorganic metal salt is one of calcium chloride, zinc chloride, zinc acetate and aluminum chloride.
Citation Information
Patent Citations
Preparation method of novel thermal radiation crosslinking semi-solid lithium battery diaphragm
CN111416087A
Cited By
High-energy-density semi-solid lithium battery and preparation method thereof
CN121964785A
High energy density semi-solid lithium battery and method of making same
CN121964785B